Severity of vertebral fracture reflects deterioration of bone microarchitecture - Genant, H. K.; Delmas, P. D.; Chen, P.; Jiang, Y.; Eriksen, E. F.; Dalsky, G. P.; Marcus, R.; San Martin, J. (Osteoporosis international, 2007)
Bone microarchitecture, a component of bone strength, is generally measured on transiliac bone biopsy samples. The objective of this study was to determine whether assessment of four grades of vertebral fracture severity could serve as a noninvasive surrogate marker for trabecular bone volume and microarchitecture. Baseline vertebral fracture severity was determined by semiquantitative assessment of spine radiographs from 190 postmenopausal women with osteoporosis. Bone-structure indices were obtained by 2D histomorphometry and 3D microcomputed tomography (CT) analyses. Significance of differences was determined after adjusting for age, height, and lumbar spine bone mineral density. There were significant (P < 0.05) trends in decreasing bone volume, trabecular number, and connectivity, and increasing trabecular separation with greater vertebral fracture severity. Histomorphometric bone volume was 25 and 36% lower (P < 0.05) in women with moderate and severe fractures than in women with no fractures, respectively. Compared with women without fractures, women with mild, moderate, and severe fractures had lower (P < 0.05) microCT bone volume (23, 30, and 51%, respectively). Microarchitectural deterioration was progressively worse in women with increasing severity of vertebral fractures. We conclude that assessment of vertebral fracture severity is an important clinical tool to evaluate the severity of postmenopausal osteoporosis.